Noninvasive ventilation: open issues for nursing research - Bambi, Stefano; Mati, Enrica; De Felippis, Christian; Lucchini, Alberto (Acta Biomedica Atenei Parmensis, 2017)
According to the current literature, Noninvasive Ventilation (NIV) is a well-recognized respiratory support technique for patients affected by Acute Respiratory Failure (ARF). As highlighted by recent meta-analysis, a tight adherence to protocols regarding patients’ selection criteria, relative or absolute contraindications, plus highly skilled and experienced operators, can positively affect the NIV performance and mortality rates. Positive outcome from NIV respiratory support is dependent from: patient’s clinical condition and education needs; confidence of the staff with NIV technology; choice and management of the most suitable interface available prevention of interface complications; nutritional assessment (artificial feeding if required) and conditioning of medical gas. Despite these issues, the air leakage represents the major threat during NIV support. Indeed, to obtain a positive outcome from this treatment, the ‘NIV troubleshooting’ management appears to be crucial. Common issues as air leakage, patient-ventilator asynchrony, interface related pressure ulcers, discomfort, and gastric distention should be promptly detected and solved. The analysis of these current issues reveals a lack of evidence based practice, resulting in bed-side clinical interventions based only on the expert consensus or local opinions. To improve this knowledge gap, more efforts are strongly recommended from medical and nursing research communities. Multicenter randomized controlled clinical trials are needed to achieve adequate knowledge to reach the best patient’s outcome. Further information to identify new areas of nursing research on NIV, can be achieved from qualitative studies performed on patients and healthcare operators.